Road traffic injuries in the Peoples Republic of China, 1951–2008. (1st March 2011) - Zhang, X; Xiang, H; Chen, Z; Jia, J; Smith, G A; Stallones, L
Abstract : Background: Road traffic injuries (RTIs) have become the leading cause of injury deaths in the P.R. China. We analysed the trends and characteristics of RTIs from 1951 to 2008. Methods: Road traffic crash data from 1951 to 2008 were obtained from the Bureau of Traffic Management at the Ministry of Public Security. All fatal traffic crashes and non-fatal traffic crashes that result in medically treated injuries are required to be reported to the Bureau of Traffic Management using a standardised traffic crash data collection form. Results: Over the past 5 decades, road traffic injuries have increased substantially in China. From 1951 to 2008, the total number of traffic crash events, traffic-related deaths and non-fatal traffic-related injuries increased by 86-fold, 125-fold and 92-fold, respectively. The traffic-related death rate increased substantially in the past 10 years and reached 5.56 per 100 000 population in 2008. Road traffic injuries in China disproportionally affect the following populations: persons 21–50 years of age, pedestrians and motorcyclists/bicyclists. RTIs among individuals older than 65 years also increased in recent years. Provinces in northern China have significantly higher traffic-related death rates than other areas of China. Conclusion: Road traffic injuries have become a burgeoning public health problem in China. Programs need to be developed to prevent injuries and fatalities caused by road traffic crashes.